2003
DOI: 10.1088/0029-5515/43/10/018
|View full text |Cite
|
Sign up to set email alerts
|

Internal transport barrier triggering by rational magnetic flux surfaces in tokamaks

Abstract: The formation of Internal Transport Barriers (ITBs) has been experimentally associated with the presence of rational q-surfaces in both JET and ASDEX Upgrade. The triggering mechanisms are related to the occurrence of magneto-hydrodynamic (MHD) instabilities such as mode coupling or fishbone activity. These events could locally modify the poloidal velocity and increase transiently the shearing rate to values comparable to the linear growth rate of ITG modes. For JET reversed magnetic shear scenarios, ITB emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(173 citation statements)
references
References 42 publications
9
162
1
1
Order By: Relevance
“…The presence of several low order rational q surfaces in this region may echo results found on several other experiments connecting ITB formation to the presence of specific low order rational q surfaces in the plasma, although it lies well inside of the q=2 and q=3/2 surfaces which have been important in other devices. 24 The rise of the central density and impurity accumulation in the ITB phase of the discharge are clamped by the addition of small amounts of central ICRF power, keeping the central Zeff level typically below 2. To date, however, exceeding a certain threshold power destroys the ITB profile.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of several low order rational q surfaces in this region may echo results found on several other experiments connecting ITB formation to the presence of specific low order rational q surfaces in the plasma, although it lies well inside of the q=2 and q=3/2 surfaces which have been important in other devices. 24 The rise of the central density and impurity accumulation in the ITB phase of the discharge are clamped by the addition of small amounts of central ICRF power, keeping the central Zeff level typically below 2. To date, however, exceeding a certain threshold power destroys the ITB profile.…”
Section: Discussionmentioning
confidence: 99%
“…Within the uncertainties of the measurement one finds that the minimum q value, q min , in the plasma is just below 2. So-called grand-cascades of Alfvén modes [18,8] have been seen in discharge 69670 at t=3.8s and another one at t~5s, while for 69668 these modes are only seen at t=3.7s. The integer q values that appear in the plasma and trigger these modes may be identified by q=3 and q=2 for the two times in 69670.…”
Section: Ex/8-3mentioning
confidence: 99%
“…This feature, identical to those observed in ref. [8,22], cannot be predicted by transport models since usually no role is given to rational surfaces. On the other hand rarefaction of rational flux surfaces, i.e.…”
Section: Ex/8-3mentioning
confidence: 99%
See 1 more Smart Citation
“…ITB's are not anything like LCS's, but indicate an experimental tokamak regime with locally, strongly reduced radial transport. 9,10 It is suggested that an ITB may be identified with broken KAM surfaces with noble values of the magnetic winding number q (Ref. 11) or that this reduced transport regime could be explained by the beneficial effect of the qprofile on the chaoticity due to a broad spectrum of magnetic perturbations.…”
Section: Phys Plasmas 18 102308 (2011)mentioning
confidence: 99%